Keefektifan Layanan Penguasaan Konten Metode Mind Mapping untuk Meningkatkan Konsentrasi Belajar - IRVAN FIRDAUZ, FAIZ RIDHLO (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
Researchers saw indications of a behavior that they can not concentrate in learning, especially some students who get the process of service delivery of guidance and conseling or in following subjects. The purpose of this study was to determine whether the service of content mastery with mind mapping method is effective to improve students' learning concentration. This type of research is pre-experimental design with one group pre-test and post-test. The subjects of this study is the whole populations of VIII-J while the method of data collection used a scale of learning concentrations psychology with using data analysis of t-test. The level of students’learning concentration before service delivery was gained an average of 56% (medium) and after delivering of services it rose to 68% (average) after delivering services the students’learning concentration increased to 12%. The result of T test showed that the t value = 4.97 with t = 2.04, it can be concluded that Ha was accepted. Research shows that services of content mastery with mind mapping method is effective to improve students' learning concentration. The suggestion which can be given is guidance and counseling teachers should be able to socialize the skills of giving the service of content mastery to increase the students’learning concentration, especially with mind mapping method.